Possibilities and limits of online interventions and psychotherapies in times of the covid-19 pandemic. Training for mental health professionals - Raúl Vaimberg Grillo (Forum for Group Psychotherapies and Processes)
We carry out a trajectory for different investigations and studies carried out in the last 15 years about psychotherapies and online interventions to conclude with the description of an online training experience developed during the year of the COVID-19 pandemic. We conducted various trainings in which 400 public and private Mental Health professionals participated in Spanish and Portuguese speaking countries. The observations about the online intervention modalities used (textual, videoconference, telephone, collective creation platforms and video games) and the type of intervention (individual, family and group) were significant. The online trainings lasted 25 hours, in groups that worked with multivideoconference by Zoom combined with a textual virtual campus, through forums, contributed articles and written work carried out by the participants. 1500 pages of text produced by students and teachers participating in the experience were recorded. Preliminary conclusions of various investigations and training experiences developed are presented.